1969
DOI: 10.1037/h0082815
|View full text |Cite
|
Sign up to set email alerts
|

Extinction following a small number of goal-box placements.

Abstract: Three experiments involved extinction of rats in a straight alley following direct placement in the goal box. Placements were given either before or after running trials in Experiments I and n. In Experiment in only placements with no alley running were given. In each case the presence of a FREE indicated the effectiveness of placements. The data are interpreted in terms of the cue effects of placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1970
1970
1980
1980

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Indeed, an experiment reported by Brown and Logan (1965) that involved extensive training and required locomotion on placement events found that the effects of the placement procedure were dependent upon the level of training. The literature is quite consistent; after a few placements both nonlocomotive and locomotive ITNs influence Rn (e.g., Brown & Logan, 1965;McCain, Baerwaldt, & Brown, 1969), whereas many placements are ineffective (e.g., Brown & Logan, 1965;Trapold & Doren, 1966) . s And as expected from the discrimination hypothesis, it takes more placement experiences with a procedure that requires running in the goal region for the intertrial nonreinforcement events to lose their effectiveness in enhancing extinction performance.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, an experiment reported by Brown and Logan (1965) that involved extensive training and required locomotion on placement events found that the effects of the placement procedure were dependent upon the level of training. The literature is quite consistent; after a few placements both nonlocomotive and locomotive ITNs influence Rn (e.g., Brown & Logan, 1965;McCain, Baerwaldt, & Brown, 1969), whereas many placements are ineffective (e.g., Brown & Logan, 1965;Trapold & Doren, 1966) . s And as expected from the discrimination hypothesis, it takes more placement experiences with a procedure that requires running in the goal region for the intertrial nonreinforcement events to lose their effectiveness in enhancing extinction performance.…”
Section: Discussionmentioning
confidence: 94%